In others' shoes: do individual differences in empathy and theory of mind shape social preferences? - Artinger, Florian; Exadaktylos, Filippos; Koppel, Hannes; Sääksvuori, Lauri (PLOS ONE, 2014)
Abundant evidence across the behavioral and social sciences suggests that there are substantial individual differences in pro-social behavior. However, little is known about the psychological mechanisms that underlie social preferences. This paper investigates whether empathy and Theory of Mind shape individual differences in pro-social behavior as conventionally observed in neutrally framed social science experiments. Our results show that individual differences in the capacity for empathy do not shape social preferences. The results qualify the role of Theory of Mind in strategic interaction. We do not only show that fair individuals exhibit more accurate beliefs about the behavior of others but that Theory of Mind can be effectively used to pursue both self-interest and pro-social goals depending on the principle objectives of a person.
Gesehen am 25.09.2020